2013
DOI: 10.1186/1475-2867-13-121
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MACC1 and c-Met in human gastric cancer and its clinical significance

Abstract: BackgroundRecent studies have suggested that the metastasis-associated colon cancer1 (MACC1) gene can promote tumor proliferation, invasion and metastasis through an upregulation of c-Met expression. However, its role in gastric cancer is controversial. Our study investigated expression of MACC1 and c-Met in gastric cancer, as well as correlated this with clinicopathological parameters.MethodsExpressions of MACC1 and c-Met protein in a sample of 98 gastric carcinoma and adjacent nontumorous tissues were detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 22 publications
2
43
0
Order By: Relevance
“…Consistent with our results, downregulation of MACC1 remarkably inhibited cell migration and invasion in gastric cancer (13), glioma (14) and ovarian cancer (15). Previous studies have demonstrated that deregulation of HGF/ c-MET signaling, governed by MACC1 induces various malignant behaviors in cancer (16).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our results, downregulation of MACC1 remarkably inhibited cell migration and invasion in gastric cancer (13), glioma (14) and ovarian cancer (15). Previous studies have demonstrated that deregulation of HGF/ c-MET signaling, governed by MACC1 induces various malignant behaviors in cancer (16).…”
Section: Discussionsupporting
confidence: 92%
“…Both HGF and c-Met are associated with progression, metastasis and survival in gastric cancer (22). Previous studies have demonstrated that MACC1, similar with c-Met, is upregulated in hepatocellular carcinoma, and that the mRNA levels of MACC1 and c-Met are significantly associated (23).…”
Section: Macc1 Was First Reported By Stein Et Almentioning
confidence: 99%
“…Retterspitz reported that MET was overexpressed in 51% (45 of 88) of diffuse type tumors [24] . MET overexpression has been significantly associated with tumor invasion depth [12,13,23] , lymph-node metastasis [12,13,19,20,25,26] , distant metastasis [12,13,25] , tumor stage [12,20,23,26] , and recurrence [14] , although several studies found no relation to any clinicopathological factors [24,27,28] . MET overexpression correlated with liver metastasis only in stage Ⅳ disease [29] .…”
Section: Protein Expression On Immunohistochemistrymentioning
confidence: 99%
“…MET overexpression correlated with liver metastasis only in stage Ⅳ disease [29] . Some studies showed that MET overexpression was an independent prognostic factor that was significantly related to poor survival [12][13][14]19,20,25,26,[30][31][32] . In one study, p-MET was detected in 59% (72 of 121) of GC tumors and was significantly associated with lymph-node metastasis, disease stage, and outcomes [20] .…”
Section: Protein Expression On Immunohistochemistrymentioning
confidence: 99%